Global Warming and Inter-Ethnic Clashes: An Ethical Evaluation of Ekiiti-Fulani Crises in Ekiti State - Olayinka Olabimpe Ojo; Folorunso Paul Olorunsola; Ayobami Olamide Akinwolemiwa (Lakhomi Journal Scientific Journal of Culture, 2023)
This paper examined the effect of Global Warming on the crises between the Fulani ethnic group and the Ekitis in Ekiti State, Nigeria. It highlighted the root causes of the tribal conflict in context to desertification, climate change, and global warming. The paper identified and documented the evolution of changes in the climate and the link to intertribal violence. The study relied heavily on documentary data and lightly on oral data. The oral data were based on newspapers. The documentary data were subjected to textual and contextual analysis. The researcher found out that the emergence of the crises correlates to global warming and climate change.